2010
DOI: 10.1039/c0ob00003e
|View full text |Cite
|
Sign up to set email alerts
|

Strain-promoted double-click reaction for chemical modification of azido-biomolecules

Abstract: The strain-promoted "double-click" (SPDC) reaction using Sondheimer diyne, a novel convergent method conjugating three molecules spontaneously, has enabled us to readily modify an azido-biomolecule with a small reporter azido-molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 40 publications
3
101
0
Order By: Relevance
“…Incubation with 10 led to efficient labelling in only 2 h, while only minor labelling was observed upon similar incubation with bis-azido-triethylene glycol reagent 11. In this respect, the here presented one-pot sequential SPAAC for labelling of a BCN-bearing protein bears resemblance, yet is nicely complementary, to the procedure reported by Hosoya et al 16 for three-component labelling of an azido-bearing protein in the presence of Sondheimer diyne and an azido-fluorophore.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Incubation with 10 led to efficient labelling in only 2 h, while only minor labelling was observed upon similar incubation with bis-azido-triethylene glycol reagent 11. In this respect, the here presented one-pot sequential SPAAC for labelling of a BCN-bearing protein bears resemblance, yet is nicely complementary, to the procedure reported by Hosoya et al 16 for three-component labelling of an azido-bearing protein in the presence of Sondheimer diyne and an azido-fluorophore.…”
Section: Resultsmentioning
confidence: 89%
“…Bicyclo[6.1.0]non-4yne (BCN, 6) is a stable, non-benzoannulated cyclooctyne that is synthetically readily accessible 15 , but generally regarded to be less reactive than DIBAC. Finally, Sondheimer diyne (7) is unique in the sense that it is able to react sequentially with two azides with distinctly different reaction rates 16 . In general it may be concluded that, despite tremendous synthetic effort, optimization of cycloaddition of azides with (stable) cyclooctynes has, depending on specific conditions, leveled off around 0.2-0.5 M À 1 s À 1 (refs 1,4).…”
mentioning
confidence: 99%
“…As a part of our studies focusing on highly strained alkynes, including arynes [24][25][26][27][28][29][30][31][32][33][34], we have been working on a project to develop new aryne generation methods. For example, we have recently succeeded in efficiently generating arynes from ortho-iodoaryl triflates bearing sensitive functional groups using a trimethylsilylmethyl Grignard reagent as an activator [30,31,33] instead of conventional activators such as n-butyllithium [35] or a turbo-Grignard reagent [36].…”
Section: Open Accessmentioning
confidence: 99%
“…1 The azido group is small, stable in biological systems, and selectively reactive with phosphines such as 1 via Staudinger ligation 2 and with cyclooctynes (e.g. 2-5) via Huisgen [3+2] cycloaddition [3][4][5][6][7][8][9][10][11] (Figure 1). …”
Section: Introductionmentioning
confidence: 99%